2006
DOI: 10.1103/physrevlett.96.205504
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study of the Diffusion of Hydrogen in ZnO

Abstract: Zinc oxide, a wide-gap semiconductor, typically exhibits n-type conductivity even when nominally undoped. The nature of the donor is contentious, but hydrogen is a prime candidate. We present ab initio calculations of the migration barrier for H, yielding a barrier of less than approximately 0.5 eV. This indicates isolated hydrogen is mobile at low temperature and that thermally stable H-related donors must logically be trapped at other defects. We argue this is also true for other oxides where H is a shallow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
170
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(187 citation statements)
references
References 36 publications
16
170
0
1
Order By: Relevance
“…Wardle et al [112] investigated the diffusion of hydrogen in ZnO from DFT calculations, finding low migration barriers, suggesting that interstitial hydrogen is indeed very mobile in ZnO. However, they suggested that hydrogen could still contribute to conductivity in ZnO, even at elevated temperatures, if it becomes trapped at other existing defect centres.…”
Section: Stabilitymentioning
confidence: 99%
“…Wardle et al [112] investigated the diffusion of hydrogen in ZnO from DFT calculations, finding low migration barriers, suggesting that interstitial hydrogen is indeed very mobile in ZnO. However, they suggested that hydrogen could still contribute to conductivity in ZnO, even at elevated temperatures, if it becomes trapped at other existing defect centres.…”
Section: Stabilitymentioning
confidence: 99%
“…Forming gas contains H, and isolated H atoms are known to move rather easily in ZnO. [8][9][10][11][12][13][14] In fact, even the most stable member of this class, substitutional H O , is believed to completely diffuse out of the sample for temperatures higher than about 475°C. 12 H can also attain stability by forming complexes with certain impurities and defects, 13 such as the Zn vacancy V Zn , 8,13 Cu, 8 and N. 14 For example, the neutral complex V Zn H 2 is stable to about 400°C.…”
Section: ͑4͒mentioning
confidence: 99%
“…11,12 In both cases, the majority of the H donor, i.e., H i + , is eliminated. 28 As a result, the carrier density is substantially lowered.…”
mentioning
confidence: 99%
“…2 Hydrogen in ZnO has been extensively studied in the last ten years 3,4,5,6,7,8,9,10,11,12,13,14,15 because unintentionally doped H is usually found in ZnO, including many commercial ZnO samples. 6 Interstitial and substitutional H have been shown by first-principles calculations to be shallow donors (i.e., + H i and + O H ), which contribute to the n-type conductivity in ZnO.…”
mentioning
confidence: 99%